1995
DOI: 10.1093/hmg/4.10.1883
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic mutations of CDKN2B and CDKN2A in primary human esophageal cancers

Abstract: The CDKN2A and CDKN2B genes, encoding p16 and p15 respectively, are located on chromosome 9p21, a locus at which frequent homozygous and heterozygous deletions occur in many primary human tumors, including esophageal carcinoma. CDKN2A and CDKN2B inhibit cyclin dependent kinase 4 (CDK4) and CDK6 and control cellular proliferation by preventing entry into the S phase of the cell cycle. Their inactivation may contribute to uncontrolled growth in human cancer. We previously described CDKN2A exon 2 mutations in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 0 publications
4
60
1
1
Order By: Relevance
“…In addition, a high frequency of mutations of CDKN2 have been observed in tissues from pancreatic adenomas (Bartsch et al , 1995), T-cell leukemias (Hebert et al, 1994), biliary tract cancers (Yoshida et al, 1995), esophageal cancers (Mori et al, 1994) and non-small cell lung cancers (Washimi e t a l., 1995;Xiao et al, 1995). In contrast to the observations in some malignancies, no deletions and rare alterations of CDKN2 were identified in breast cancers (Xu et al, 1994), malignant mesothelioma (Cheng et al, 1994), small cell lung cancers (Okamoto et al, 1995), head and neck cancers (Zhnag et al, 1994), thyroid cancers ( Tung et al, 1996), ovarian cancers (Campbell et al , 1995;Rodabaugh et al, 1995) and esophageal cancers (Okamoto et al, 1994;Suzuki et al, 1995). In some tumors, especially the reported mutation frequency of C D K N 2 was controversial, varying from 0 to 52% in esophageal carcinomas (Mori et al, 1994; Okamoto et a l., 1994;Suzuki et al, 1995), 7 to 83% in non-small cell lung cancers (de-Vos et al, 1995;Nakagawa et al , 1995;Xiao et al, 1995), and 4 to 36% in B-ALL (Schroder et al, 1995;Guidal-Giroux et al, 1996).…”
mentioning
confidence: 80%
“…In addition, a high frequency of mutations of CDKN2 have been observed in tissues from pancreatic adenomas (Bartsch et al , 1995), T-cell leukemias (Hebert et al, 1994), biliary tract cancers (Yoshida et al, 1995), esophageal cancers (Mori et al, 1994) and non-small cell lung cancers (Washimi e t a l., 1995;Xiao et al, 1995). In contrast to the observations in some malignancies, no deletions and rare alterations of CDKN2 were identified in breast cancers (Xu et al, 1994), malignant mesothelioma (Cheng et al, 1994), small cell lung cancers (Okamoto et al, 1995), head and neck cancers (Zhnag et al, 1994), thyroid cancers ( Tung et al, 1996), ovarian cancers (Campbell et al , 1995;Rodabaugh et al, 1995) and esophageal cancers (Okamoto et al, 1994;Suzuki et al, 1995). In some tumors, especially the reported mutation frequency of C D K N 2 was controversial, varying from 0 to 52% in esophageal carcinomas (Mori et al, 1994; Okamoto et a l., 1994;Suzuki et al, 1995), 7 to 83% in non-small cell lung cancers (de-Vos et al, 1995;Nakagawa et al , 1995;Xiao et al, 1995), and 4 to 36% in B-ALL (Schroder et al, 1995;Guidal-Giroux et al, 1996).…”
mentioning
confidence: 80%
“…An obvious source of concern was that the interaction Yoshida et al, 1995;Sou®r et al, 1998) (Liu et al, 1995) (Zhang et al, 1994;Liu et al, 1995;Pollock et al, 1995;Platz et al, 1997) (Walker et al, 1995;FitzGerald et al, 1996;Flores et al, 1997;Harland et al, 1997;Sun et al, 1997;Sou®r et al, 1998) (Hussussian et al, 1994) (Hayashi et al, 1994;Komiya et al, 1995;Liu et al, 1995;Tamimiet al, 1996) (Hayashi et al, 1994;Mori et al, 1994;Zhang et al, 1994) (Hayashi et al, 1994) (Ohta et al, 1994;Pollock et al, 1995) (Hayashi et al, 1994) (Hussussian et al, 1994;Kamb et al, 1994;Whelan et al, 1995;Sou®r et al, 1998) (Borg et al, 1996;Platz et al, 1997) (Harland et al, 1997) (Yoshida et al, 1995) (Okamoto et al, 1994;Gonzalez-Zulueta et al, 1995;Suzuki et al, 1995) (Hayashi et al, 1994;Marchetti et al, 1997) The variant forms of p16 INK4a are identi®ed by the residue number¯anked by the wild-type and variant amino acids in single letter code. Thus, L16P refers to the substitution of proline for leucine at position 16.…”
Section: Ectopic Expression Of P16 Ink4a Variants In Tig-er Cellsmentioning
confidence: 99%
“…A127S was already considered to be a polymorphism because of its presence in una ected tissues (Okamoto et al, 1994;GonzalezZulueta et al, 1995;Suzuki et al, 1995) and from functional data (Koh et al, 1995). Since A127 is on the surface of the protein, away from the CDK interacting domains, addition of an oxygen atom, as in A127S, would be readily tolerated.…”
Section: Relative Merits Of Functional Assays For P16 Ink4amentioning
confidence: 99%
“…It contains 3 coding exons (Serrano et al, 1993) and encodes a 156-amino-acid protein, previously identified as a cyclindependent kinase (CDK) inhibitor that has capacities to bind CDK4 and CDK6 and to inhibit cellular proliferation by preventing entry into the S phase of the cell cycle (Serrano et al, 1993;Lukas et al, 1995). This gene is homozygously deleted or mutated in a variety of cell lines derived from tumors and has been proposed to constitute a potential target of point mutations and deletions in primary human tumors (Pollock et al, 1996).There is a controversy regarding the implication of p16 gene alterations in the development of esophageal cancers (Mori et al, 1994;Okamoto et al, 1994;Zhou et al, 1994;Igaki et al, 1995;Liu et al, 1995;Suzuki et al, 1995; Esteve et al, 1996;Maesawa et al, 1996). The present study was thus undertaken to determine the prevalence of LOH on chromosome 9 and p16 mutation in both Barrett's adenocarcinoma (BA) and SCC of the esophagus.…”
mentioning
confidence: 99%
“…There is a controversy regarding the implication of p16 gene alterations in the development of esophageal cancers (Mori et al, 1994;Okamoto et al, 1994;Zhou et al, 1994;Igaki et al, 1995;Liu et al, 1995;Suzuki et al, 1995;Esteve et al, 1996;Maesawa et al, 1996). The present study was thus undertaken to determine the prevalence of LOH on chromosome 9 and p16 mutation in both Barrett's adenocarcinoma (BA) and SCC of the esophagus.…”
mentioning
confidence: 99%